Knowledge and Practice Regarding Prevention of Myocardial Infarction among People above 40 Years of Age - Chalise, Sarmila; Kalakheti, Kamal; Adhikari, Sudip; Khanal, Saraswati; Upadhyay, Hari Prasad; Sedain, Prativa (Journal of National Heart and Lung Society Nepal, 2023)
Background: : This study entitled " Knowledge and Practice Regarding Prevention of Myocardial Infarction Among People Above 40 Years of Age" was carried out to identify the knowledge and practice regarding prevention of myocardial infarction among people above 40 years of age attending in community people. Methodology: Simple descriptive cross sectional study design was used for the study conducted in the Siddharthanagar Municipality,-09 no-ward with a sample of 138 and were selected by Non-probability purposive sampling technique using semi-structured questionnaire. Result: The study revealed that majority (61.6%) were age 40-50 years, majority (60.9%) were male. Majority (81.9%) of Hindu were found. Majority were literate (60.9%); out of them, highest number (30.4%) had secondary level education. Majority of (60.1%) were farmer depending upon Agriculture. The majority (100%) Heard about Heart attack (MI) and mostly (50.0%) received information through Media\TV. (30.4) participants believed that MI is curable and controllable. However, (95.7%) were unknown about anyone who had heart attack before and majority (79.7%) hadn't ever received any information related MI. Majority (70.3%) Sudden pain or discomfortable in the chest and (64.5%) had chest pain through Identify and characteristics Symptoms of MI. Majority believed (47.1%) risk factor were smoking. (100%) believed that it requires a prompt treatment, (71.0%) take them hospital immediate. Highest number (77.5%) believed that lack of exercise is major factor and (81.9) heart disease, (91.3) hypertension were risk for MI. (87.7%) believed that less fat more fruits and vegetables should be consumed on daily basis whereas (100%) had no stress and (52.9%) were stay happy. Conclusion: The study found that 61.9% of respondents were literate, while 39.1% were illiterate but the majority (100%) were aware of heart attack (MI), which is curable and controllable. Nepal needs to conduct awareness programmes for MI and prevent life-threatening diseases.